Pengembangan Gerakan Beladiri KARATE SHOTO-KAN Berbasis Animasi Menggunakan Kombinasi Unity dengan Teknologi AR - Muhammad Al Khawarizmi Rangkuti; Ari Usman (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Shoto-Kan Karate is a martial art style that emphasizes technique and precision of movement. However, in the traditional learning process, limited visual interaction and demonstration of movements often become obstacles, especially for beginners who do not have a permanent trainer. To address this problem, this study aims to develop interactive learning media based on Shoto-Kan Karate movement animations by utilizing Augmented Reality (AR) technology built using Unity. Test results show that the application runs well on various Android devices and receives positive responses from users, especially in terms of ease of understanding the movements, animation precision, and interactivity offered. In conclusion, the use of Unity-based AR technology is effective in improving the understanding and experience of independent learning of Shoto-Kan Karate. This media can be an innovative solution in the world of martial arts education, especially in today's digital era.